Mass Tracking in Cellular Networks for the COVID-19 Pandemic Monitoring. - Khatib, Emil Jatib; Perles-Roselló, María Jesús; Miranda-Páez, Jesús; Giralt García, Victoriano; Barco-Moreno, Raquel (MDPI, 2021)
The year 2020 was marked by the emergence of the COVID-19 pandemic. After months of uncontrolled spread worldwide, a clear conclusion is that controlling the mobility of the general population can slow down the propagation of the pandemic. Tracking the location of the population enables better use of mobility limitation policies and the prediction of potential hotspots, as well as improved alert services to individuals that may have been exposed to the virus. With mobility in their core functionality and a high degree of penetration of mobile devices within the general population, cellular networks are an invaluable asset for this purpose. This paper shows an overview of the possibilities offered by cellular networks for the massive tacking of the population at different levels. The major privacy concerns are also reviewed and a specific use case is shown, correlating mobility and number of cases in the province of Málaga (Spain).
Keywords: Sistemas de comunicación inalámbricos; COVID-19; Location; Cellular networks; Pandemic